Future Developments of Medical Informatics from the Viewpoint of Networked Clinical Research - Ohmann, C.; Kuchinke, W. (Methods of Information in Medicine, 2009)
Objectives: To be prepared for future developments, such as enabling support of rapid innovation transfer and personalized medicine concepts, interoperability of basic research, clinical research and medical care is essential. It is the objective of our paper to give an overview of developments, indicate problem areas and to specify future requirements.Methods: In this paper recent and ongoing large-scaled activities related to interoper-ability and integration of networked clinical research are described and evaluated. The following main topics are covered: necessity for general IT-conception, open source/open community approach, acceptance of eSource in clinical research, interoperability of the electronic health record and electronic data capture and harmonization and bridging of standards for technical and semantic inter-operability.Results: National infrastructures and programmes have been set up to provide general IT-conceptions to guide planning and development of software tools (e.g. TMF, ca BIG, NIHR). The concept of open research described by transparency achieved through open access, open data, open communication and open source software is becoming more and more important in clinical research infrastructure development (e.g. ca BIG, ePCRN). Meanwhile visions and rules for using eSource in clinical research are available, with the potential to improve interoperability between the electronic health record and electronic data capture (e.g. CDISC e SDI, eClinical Forum/PhRMA EDC/eSource Taskforce). Several groups have formulated user requirements, use cases and technical frameworks to advance these issues (e.g. NHIN Slipstream-project, EHR/CR-project, IHE). In order to achieve technical and semantic interoperability, existing standards (e.g. CDISC) have to be harmonized and bridged. Major consortia have been formed to provide semantical inter-operability (e.g. HL7 RCRIM under joint leadership of HL7, CDISC and FDA, or BRIDG covering CDISC, HL7, FDA, NCI) and to provide core sets of data collection fields (CDASH).Conclusions: The essential tasks for medical informatics within the next ten years will now be the development and implementation of encompassing IT conceptions, strong support of the open community and open source approach, the acceptance of eSource in clinical research, the uncompromising continuity of standardization and bridging of technical standards and the widespread use of electronic health record systems.
Keywords: Interoperability; open source; eSource; electronic health record; electronic data capture; standards; CDISC; caBIG; HL7